The Effectiveness of E-WOM (Electronic Word Of Mouth) and Instagram Social Media Promotion on Purchase Intention at Liang Teh Sumatera - Widuta, Lara; Muammar Rinaldi (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
The purpose of this research is to investigate the influence of e-wom on the purchase intention of customers at Liang Teh Sumatera, as well as the influence of Instagram social media promotion on their purchase intention. The study involves a population of 8,280 customers at Liang Teh Sumatera using a descriptive quantitative method. Sample size was calculated using Slovin's method at a 10% margin of error, giving 99 participants. Various research instruments including direct observation, literature review and respondent questionnaires were used to collect data. Multiple linear regression analysis was used to analyze the data. Multiple linear regression analysis was used to formulate and test three hypotheses in this study. The results of this study indicate that the effectiveness of e-wom and Instagram social media promotion has a significant impact on customers' purchase intentions.